Structural and immunogenicity analysis of reconstructed ancestral and consensus P48/45 for cross-species anti malaria transmission-blocking vaccine. (June 2021) - Ramanto, Kevin Nathanael; Nurdiansyah, Rizky
Abstract: The development of the anti-malaria vaccine holds a promising future in malaria control. One of the anti-malaria vaccine strategies known as the transmission-blocking vaccine (TBV) is to inhibit the parasite transmission between humans and mosquitoes by targeting the parasite gametocyte. Previously, we found that P48/45 included in the 6-Cysteine protein family shared by Plasmodium sp. We also detected vaccine properties possessed by all human-infecting Plasmodium and could be used as a cross-species anti-malaria vaccine. In this study, we investigated the efficacy of P48/45 through the ancestral and consensus reconstruction approach. P48/45 phylogenetic and time tree analysis was done by RAXML and BEAST2. GRASP server and Ugene software were used to reconstruct ancestral and consensus sequences, respectively. The protein structural prediction was made by using a psipred and Rosetta program. Each protein characteristic of P48/45 was analyzed by assessing hydrophobicity and Post-Translational Modification sites. Meanwhile, the Epitope sequence for B-cell, T-cell, and HLA was determined using an immunoinformatics approach. Lastly, molecular docking simulation was done to determine native binding interactions of P48/45-P230. The result showed a distinct protein characteristic of ancestral and consensus sequences. The immunogenicity analysis revealed the number of epitopes in the ancestral sequence is greater than the consensus sequence. The study also found a conserved epitope located in the binding site and consists of specific Post-Translational Modification sites. Hence, our research provides detailed insight into ancestral and consensus P48/45 efficacy for the cross-species anti-malaria vaccine.